60.9k views
5 votes
6. (-3k + 4) + 3(2k – 3)
What is this

User Ben Golden
by
5.4k points

2 Answers

2 votes

Answer:

k = 5/3

Explanation:

1. Distribute the 3 to 2x and -3

(-3k + 4) + (6k - 9) = 0

2. Since we're adding (you can always do this when subtracting/adding parantheses), you can remove the parentheses. They do nothing extra to the equation.

-3k + 4 + 6k - 9 = 0

3. Add like terms (k's and whole numbers)

3k - 5 = 0

4. To solve for K, we need to add 5 to both sides of the equation.

3k = 5

5. Divide both sides by 3.

k = 5/3

Use this step by step solution to find whatever you're looking for.

User RolandXu
by
5.1k points
4 votes

Answer:

Explanation:

(-3k + 4) + 3(2k – 3) = - 3k + 4 + 3*2k - 3*3

= -3k + 4 + 6k - 9

= 3k - 5

When two numbers are in different sign, subtract and the result will carry sign of the bigger number.

User Scott Yang
by
4.8k points